Avaliação da infecção experimental de cães com membranas córion-alantóides de Gallus gallus inoculadas com Neospora caninum - Munhoz, Alexandre Dias; Mineo, Tiago Wilson Patriarca; Alessi, Antonio Carlos [UNESP]; Lopes, Carlos Wilson Gomes; Machado, Rosangela Zacarias [UNESP] (My University, 2013)
The aim of this study was to evaluate parasitism kinetics and tissue lesions in the first week of infection by Neospora caninum in dogs fed Gallus gallus chorioallantoic membranes (CMs) previously infected in ovo. Five two-month-old pups were used. Each dog was given five CMs that were previously infected with N. caninum via the oral route. Four animals were euthanized in the first week of infection. All four dogs had their stools examined one week prior to and up to the day they were euthanized. The stools of the uneuthanized dog were collected for 30 days. After euthanasia, organ sections were utilized for histopathology, immunohistochemistry, indirect immunofluorescent tissue reactions, PCR and real-time PCR to detect parasites. Necropsy revealed that the small and large intestines, spleen, and lungs were affected. No oocysts or N. caninum DNA were identified in the stool samples. Real-time PCR was the most sensitive technique used to detect the protozoa in tissues, which were identified in 41% of the analyzed samples. Our results indicate that an experimental model using previously infected CMs appears to be a useful model for the study of the host-parasite relationship during the infection's acute phase.
Assessment of experimental infection for dogs using Gallus gallus chorioallantoic membranes inoculated with Neospora caninum
Keywords: Acute phase; Immunohistochemistry; Infection; Neosporosis; Real-time pcr